2011
DOI: 10.1007/s12149-011-0474-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of FDG-PET for preoperative evaluation of endometrial cancer

Abstract: FDG-PET had a reasonably high diagnostic accuracy in endometrial cancer. Although the number of cases with clinical impact was limited, additional information by PET was obtained in one-third of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The spectra of patients included in the current meta-analysis were not wide enough for evaluation of specificity. Actually only 4 studies evaluated the specificity, 25,29,32,34 and 2 of them included only patients with physiological uterine activity without any endometrial tumoral lesion for this purpose. 25,32 Future studies should be conducted on a wide range of patients with factors suggestive of endometrial cancer for better evaluation of specificity.…”
Section: Detection Of Primary Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra of patients included in the current meta-analysis were not wide enough for evaluation of specificity. Actually only 4 studies evaluated the specificity, 25,29,32,34 and 2 of them included only patients with physiological uterine activity without any endometrial tumoral lesion for this purpose. 25,32 Future studies should be conducted on a wide range of patients with factors suggestive of endometrial cancer for better evaluation of specificity.…”
Section: Detection Of Primary Tumormentioning
confidence: 99%
“…Potential locations and pathologies with 18 F-FDG uptake that could cause false-positive studies were as follows: benign lung lesions, 18,22 bowels, 18 second malignancies, 19,22,29 colon adenoma, 22 and reactive lymph nodes (besides pelvic and para-aortic lesions). 22,27 Limitations Heterogeneity of included studies is an important issue that should be addressed in all meta-analyses.…”
Section: Distant Metastasesmentioning
confidence: 99%
“…It is important to know or predict the stage of disease before the operation to perform full staging surgery. In previous studies, it was found that PET/CT has moderate sensitivity and high specificity for detecting nodal metastasis (29)(30)(31) and high sensitivity and specificy for detecting metastatic disease (32). Authors concluded that PET/CT is not a substitute for lymphadenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated positron emission tomography/CT (PET/ CT) with 18 F-fluorodeoxyglucose (FDG) that gives combined metabolic and anatomical information together in a single session allows the assessment of endometrial tumours [14] . 18 F-FDG PET/CT is a non-invasive diagnostic method that helps to image tumor distribution and metabolism in various malignancies.…”
Section: Introductionmentioning
confidence: 99%